The Effect of Submerged Vanes on Improving Hydraulic Jump Characteristics and Investigating the Role of Attack Angle - M. Heidarpour; Kimia Akhavan; N. Pourabdollah (علوم آب و خاک)
One of the ways to improve the characteristics of the hydraulic jump in the stilling basin is to use natural and artificial roughness. Recently, due to the advantages of immersed plates compared to other non-continuous artificial roughness, such as the smaller number of these and the vanes' ability to design their geometry and arrangement, it has been approached more. In this article, the effect of submerged vanes with three contact angles of 45°, 75°, and 90° has been investigated on the improvement of the characteristics of a hydraulic jump and its effect on parameters such as the depth ratio, relative length, energy loss rate, and bed shear force coefficient has been evaluated. The results of this research showed that the average effect of submerged vanes on reducing the depth ratio, jump length, and roller length compared to the classical mode is 9.4%, 24.6%, and 28.4%, respectively and the average relative energy loss is 5.5% compared to the classical state and maximum relative energy loss at the angle of 90 degrees of submerged vanes is 6.5%. Considering these results and other conditions such as ease of construction and use, stabilization, and ‌reduction of economic costs among the available choices of sunken vanes, the angle of incidence of 75° is a suitable option for the optimal design of the stilling basin.